Development of a mineral binding material with elevated content of red mud - Cherniak, Lev; Varshavets, Petro; Dorogan, Nataliia (Technology audit and production reserves, 2017)
The object of present research is the technology of production of mineral binding materials of low-temperature (Tmax=1100 ºC) roasting of the romancement type with maximal possible use of waste from alumina production – red mud as a technogenic raw material. We employed as research methods a combination of computer calculations using the new software, modern physical-chemical methods of analysis and standardized testing of the properties of raw materials and binding materials. Based on computer calculations, applying the developed software «RomanCem», we performed analysis of dependence of the concentration of red mud in 3-component blends on the number of hydraulic module of the binder NM=1.1–1.7. We determined compositions of blends containing red mud of 27.0–27.5 % by weight (versus 3–5 % by weight in the technology of Portland cement) for the production of a hydraulic mineral binder at a maximum temperature of roasting 1100 ºC (versus 1400–1450 ºC for Portland cement) with improved indicators of strength at 18–22 MPa (versus 5–10 MPa for romancement). Effectiveness of our technique is defined by a comprehensive solution to the issues of ecology (due to reducing the volumes of waste accumulation), resource saving (through a replacement with waste of part of the raw materials of natural origin), and technology of binders (due to obtaining a product of the romancement type with improved indicators of properties). We demonstrated the features of phase composition and properties of the binders based on the systems of carbonate component with polymineral clay, quartz powder and red mud.